Influence of 𝑳𝒊+ Substitution on Magnetic and Electrical Properties of 𝑳𝒊𝒙𝑪𝒖𝟎.𝟓𝒁𝒏𝟎.𝟓−𝟐𝒙𝑭𝒆𝟐+𝒙𝑶𝟒 - Mustafa, Anjum (Brac University, 2020)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics, 2019.